1999: The slaughter of El placer or the political problem of the memory and the forgiveness (2017)
This paper attempts to analyze the case of the regime paramilitary which was victim the community of El Placer between 1999 and 2006. This essay has two main objectives. The first is to use some testimonies of the survivors to provide an overview of the hostile environment in which the population lived. Here, I pretend to emphasize, especially, the harm and the perpetration on the women. The second objective is to analyze the Colombian problem of the memory, the politics and the forgiveness through the notion of the differend (différend), concept proposed and developed by the philosopher Jean F. Lyotard. My impression is that, from this point of view, we can criticize (i) the lack of participation of the Colombian State in the armed conflict places, and (ii) the solutions that, through of the law and the model of transitional justice of this period, were propose to solve the harm of the victims. More than venture a thesis, this text is an attempt to approach a rather recurring problem in the current academics discussions in Colombia: How to deal with the problem of the reconciliation between the victims and the victimizers where what prevails is the recognition of a harm that, in principle, is unforgivable?